Moda que no incomoda: Desarrollo estratégico de campaña para un consumo de ropa responsable (2022)
This degree project is based on the creation of a campaign to make visible the current problems of "Fast Fashion", the consequences of consumption, and the uncontrolled production on the environment. It also seeks to communicate the alternatives that exist to counteract this impact.